Comprehensive environmental impact evaluation for concrete mixing station (CMS) based on improved TOPSIS method. (June 2021) - Lin, Song-Shun; Shen, Shui-Long; Zhang, Ning; Zhou, Annan
Highlights: Approach related to improved TOPSIS method is developed. Framework of comprehensive environmental impact evaluation of CMS is proposed. Influential factors of CMS regarding on environmental impacts are summarized. A case study related to CMS optimal location evaluation is illustrated. Developed approach provides a guideline in decision making for cleaner production evaluation. Abstract: This study presents an approach based on the improved technique for order preference by similarity to an ideal solution (TOPSIS) to perform comprehensive environmental impact evaluation for concrete mixing station (CMS) and to determine the optimal location of CMS. An evaluation framework consisting of four indicators and 12 sub-indicators from the environmental and sustainable aspects is established. Entropy method is adopted to determine the weights of indicators and sub-indicators. The improved TOPSIS method is employed to rank candidate locations according to the values of closeness coefficient index (CCI). A case study regarding on CMS location selection of a tunnel project is demonstrated the performance of developed approach. Results show that factors, i.e. environmental impact and pollution reduction management, are top two indicators which should be paid more attention. Moreover, the ranking order of candidate location is presented. Sensitivity and comparison analysis indicate that ranking results considering only profitability indicators is opposite that the results in only consumption indicators. The developed approach provides a guideline in MCS management to increase the sustainability of city.